Pathogenic mechanism of recurrent mutations of SCN8A in epileptic encephalopathy. Issue 2 (21st December 2015) - Wagnon, Jacy L.; Barker, Bryan S.; Hounshell, James A.; Haaxma, Charlotte A.; Shealy, Amy; Moss, Timothy; Parikh, Sumit; Messer, Ricka D.; Patel, Manoj K.; Meisler, Miriam H.
Abstract: Objective: The early infantile epileptic encephalopathy type 13 (EIEE13, OMIM #614558) results from de novo missense mutations of SCN8A encoding the voltage‐gated sodium channel Nav 1.6. More than 20% of patients have recurrent mutations in residues Arg1617 or Arg1872. Our goal was to determine the functional effects of these mutations on channel properties. Methods: Clinical exome sequencing was carried out on patients with early‐onset seizures, developmental delay, and cognitive impairment. Two mutations identified here, p.Arg1872Leu and p.Arg1872Gln, and two previously identified mutations, p.Arg1872Trp and p.Arg1617Gln, were introduced into Nav 1.6 cDNA, and effects on electrophysiological properties were characterized in transfected ND7/23 cells. Interactions with FGF14, G‐protein subunit G βγ, and sodium channel subunit β 1 were assessed by coimmunoprecipitation. Results: We identified two patients with the novel mutation p.Arg1872Leu and one patient with the recurrent mutation p.Arg1872Gln. The three mutations of Arg1872 and the mutation of Arg1617 all impaired the sodium channel transition from open state to inactivated state, resulting in channel hyperactivity. Other observed abnormalities contributing to elevated channel activity were increased persistent current, increased peak current density, hyperpolarizing shift in voltage dependence of activation, and depolarizing shift in steady‐state inactivation. Protein interactions were not affected. Interpretation: Recurrent mutations at Arg1617 and Arg1872 lead to elevated Nav 1.6 channel activity by impairing channel inactivation. Channel hyperactivity is the major pathogenic mechanism for gain‐of‐function mutations of SCN8A . EIEE13 differs mechanistically from Dravet syndrome, which is caused by loss‐of‐function mutations of SCN1A . This distinction has important consequences for selection of antiepileptic drugs and the development of gene‐ and mutation‐specific treatments.